2018
DOI: 10.1002/pep2.24077
|View full text |Cite
|
Sign up to set email alerts
|

Identification of an IDR peptide formulation candidate that prevents peptide aggregation and retains immunomodulatory activity

Abstract: Synthetic peptides derived from naturally occurring host defence peptides (HDPs) have garnered significant attention as novel pharmaceuticals, particularly as alternatives to antibiotics and for immunomodulatory applications. One of the barriers to advancing synthetic peptides for therapeutic applications is their tendency to aggregate under specific ionic conditions similar to those they would encounter in vivo. Formulating peptides with biocompatible excipients that prevent solvent‐induced peptide aggregatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 48 publications
1
13
0
Order By: Relevance
“…Similarly, Haney et al found that derivatized HPGs containing a hydrophobic polymer core capped with carboxylic acid-functionalized PEG groups significantly reduced the aggregation of the synthetic AMP IDR-1018 both in vitro and in vivo while maintaining the immunomodulatory activity of the peptide [132]. This is of particular interest as peptide aggregation has been shown to inhibit the activity of certain AMPs and is thought to be partially responsible for AMP toxicity [99,132]. Notably, this formulation did not require covalent conjugation or modification of the parent peptide and was more efficacious than other tested formulations utilizing hyaluronic acid, carboxymethyl cellulose, and hydroxypropyl methyl cellulose.…”
Section: Synthetic Polymersmentioning
confidence: 93%
See 1 more Smart Citation
“…Similarly, Haney et al found that derivatized HPGs containing a hydrophobic polymer core capped with carboxylic acid-functionalized PEG groups significantly reduced the aggregation of the synthetic AMP IDR-1018 both in vitro and in vivo while maintaining the immunomodulatory activity of the peptide [132]. This is of particular interest as peptide aggregation has been shown to inhibit the activity of certain AMPs and is thought to be partially responsible for AMP toxicity [99,132]. Notably, this formulation did not require covalent conjugation or modification of the parent peptide and was more efficacious than other tested formulations utilizing hyaluronic acid, carboxymethyl cellulose, and hydroxypropyl methyl cellulose.…”
Section: Synthetic Polymersmentioning
confidence: 93%
“…Though the activity of the peptide did decrease, the most promising conjugate, a low molecular weight HPG containing 7-8 conjugated peptides, still displayed moderate activity in vitro against S. aureus. Similarly, Haney et al found that derivatized HPGs containing a hydrophobic polymer core capped with carboxylic acid-functionalized PEG groups significantly reduced the aggregation of the synthetic AMP IDR-1018 both in vitro and in vivo while maintaining the immunomodulatory activity of the peptide [132]. This is of particular interest as peptide aggregation has been shown to inhibit the activity of certain AMPs and is thought to be partially responsible for AMP toxicity [99,132].…”
Section: Synthetic Polymersmentioning
confidence: 94%
“…Peptide 1018 aggregated (and/or formed hydrogels) in a concentration-dependent manner in buffers containing certain anions, particularly phosphate, benzoate, citrate, and nitrate, according to the Hofmeister series of anions, whereas altering the cation had little effect except at very high concentrations. It also co-precipitated serum proteins in tissue culture medium [27] and demonstrated precipitation in vivo using a mouse skin injection model [28]. This latter observation might explain the toxicity of certain peptides due to their precipitation in the blood when applied intravenously.…”
Section: Challenges Facing Clinical Application Of Anti-biofilm Peptidesmentioning
confidence: 94%
“…Inconsistencies between in vitro and in vivo efficacy might be explained by physiological conditions within the host influencing stability and toxicity of anti-biofilm peptides and thus indirectly interfering with their activity. For instance, 1018 has been shown to precipitate in vitro in the presence of mucin and ions as well as when injected subcutaneously into mice [27,28]. In another study, topical application of the rationally de-DOI: 10.1159/000491497 signed peptide DRGN-1 significantly reduced wound size in a mixed biofilm-infected murine wound model [22].…”
Section: In Vivo Activity Of Anti-biofilm Peptidesmentioning
confidence: 99%
See 1 more Smart Citation